PERTANGGALAN ABSOLUT SITUS KUBUR KALANG : SIGNIFIKASINYA BAGI PERIODISASI KUBUR PETI BATU DI DAERAH BOJONEGORO DAN TUBAN, JAWA TIMUR - Handini, Retno (BRIN, 2003)
Our absolute dating for the Kubur Kalang culture is the first date obtained from this cultural group. The results show the numbers 1420 AD to 1620 AD. This means that the Kalang Burials in Bojonegoro is a prehistoric tradition, which is still practiced by a group of people. If this dates are applied in the historical framework in Java, the oldest number (1420 AD) will fall to the reign of Bhre Hyang Purwawicesa as one of the kings in the Girindrawardhana dynasty from the end of the Majapahit kingdom period, while the youngest figure (1620 AD) will refer to the middle of the Sultan Agung's reign from the Islamic Mataram kingdom. The implication is that the supporter of Kubur Kalang culture in Bojonegoro could be the burial of common people when Hindu culture has entered and developed in Indonesia, such as indicated by Stutterheim, or even during the reign of Sultan Agung.